Polymorphous Adenocarcinoma of Lacrimal Gland: A Rare Case Report - Osama, Md Ali; Rao, Seema; Grover, A K (Annals of Pathology and Laboratory Medicine, 2021)
Polymorphous adenocarcinoma is a slow growing malignant tumor of minor salivary glands. The most common location of these tumors is palate, buccal mucosa, upper lip, floor of mouth and retromolar region. This malignant neoplasm is characterized by cytological uniformity, architectural diversity and infiltrative growth pattern. This is a case report of polymorphous adenocarcinoma occurring in lacrimal gland. They are seldom reported in this location and propose unique diagnostic challenges.